Effects of Boko Haram Insurgency on Basic Education in the Southern Part of Borno State of Nigeria - Isah Abubakar (Recent Trends in Social Studies, 2025)
A place's level of educational development is determined by its society. The standard of education given determines a society's degree of political, economic, technological, religious, and cultural growth. The purpose of the study is to examine how the Boko Haram insurgency affects universal basic education (U.B.E.) in the southern region of Borno state, which is affected by the insurgency in many ways. The researchers want to consider the mayhem of the rebellions on Universal Basic Education (UBE). Forty-five basic schoolteachers, one from each of the nine local government units in the southern region of the state, made up the research sample. The research will pinpoint the difficulties the insurgency presents, explain its historical background, and set clear goals for progress. The study concept will be supported by a comprehensive evaluation of pertinent literature, and a comprehensive methodology will be used to collect data. The main methods for obtaining data from participants in nine local government regions will be questionnaires and interviews. Basic descriptive statistics will be used to evaluate the data in order to clearly illustrate the impact of the insurgency. Additionally, the study aims to provide practical suggestions to lessen the negative impacts of the insurgency on the advancement of education. In order to ensure the U.B.E. program's sustainability and efficacy in areas affected by war, this study intends to help develop ideas for improving the program's functioning and resilience in the face of such obstacles.
Keywords: Boko Haram; basic education; educational resilience; impact on education; insurgency